Rational Intervention Public Policy for Public Service Innovation - Dewi Maharani; Lesmana Rian Andhika (Indonesian Association for Public Administration, 2021)
This study aims to discuss and compare population administration innovations in two different regencies to gain an understanding of how policies can intervene in public service innovations. Innovation is dependent on government policy as a guide for good public service development strategies. Policy intervention in public service innovation gives special attention to the coherent implementation of public service innovations. The policy will affect further innovation development alth o ugh i t c an be exc lud e d f ro m s o me i nnovati o n pro grams . Therefore, this research compares the innovation efforts of population administration in two different regencies to gain a better understanding of how policies intervene in public service innovation. This research was conducted in the Aceh Tenggara and Majalengka regencies in May-June 2019. Qualitative methods were used in this research with a comparative analysis (Qualitative Comparative Analysis). Data was obtained through a cross-sectional study and data analysis using a set and concept technique. With a theoretical guide developed by Hartley (2005), this research provides information that not all regency (government institutions) can innovate for a variety of reasons, and that decision-makers must be transformative leaders for their region in order to bring out the idea of innovation. In addition, managers should be able to translate policy intent and objectives with service programs. Further development of public service innovations and citizen participation is needed as respondents and external supervisors. That way policy interventions can provide opportunities for change in government institutions by reviewing policy goals and objectives, as well as the linkage factor between local and national policies being the main consideration.